How far is FDI relevant to India's foreign trade growth? An empirical investigation - Shib Sankar Jana; Tarak Nath Sahu; Krishna Dayal Pandey (Journal of Economic Structures, 2020)
The study seeks to foster fresh empirical evidence on how FDI is relevant to the foreign trade growth in India under a time-varying parameter model with vector autoregres-sive specification. The Johansen's cointegration test documents a significant and posi-tive long-run co-movement between FDI and foreign trade in India. The vector error correction model suggests a unidirectional long-run causality from foreign trade to FDI. However, the Granger causality test confirms a bidirectional short-run causal relation-ship between these variables. Further, the variance decomposition analysis approves strong exogeneity of foreign trade. Again, the impulse response function analysis reveals that the responses generated from a positive shock of foreign trade to FDI and vice versa are small and initially negative and thereafter remain persistently positive at a constant level. The study finally concludes that the absence of long-run causality from FDI to export is the result of much domestic market orientation of foreign investors and less emphasis on the export-oriented sectors in India.
Keywords: F13; F14; F21; C22; 330; Foreign direct investment; Foreign trade; Export; Vector autoregressive specification